Analysis of preschool children's drawings using the developmental approach - De Leon, Catherine Q. (EDUKASYON, 1997)
"Using the developmental approach as applied in Art Education, the study examined drawings made by scribblers and preschematic preschool children. A group of children in the scribbling stage and another group in the preschematic stage of drawing development were monitored and documented. Every dot, line and figure that the subjects made were taken into account.